High gain MIMO antenna with multiband characterization for terahertz applications - Youssef Amraoui; Imane Halkhams; Rachid El Alami; Mohammed Ouazzani Jamil; Hassan Qjidaa (Scientific African)
Recently, the relevance of multiple input multiple output (MIMO) technology has increased due to the growing user base and the surge in demand for high data rates. It provides an essential answer to the pressing requirement for high-capacity communication systems compliant with new standards. In this study, a four-element MIMO antenna with specific properties—a thickness of 0.0224 mm and a relative permittivity of 4.3 —is presented on a polyamide substrate. It is intended to operate in terahertz (THz) applications at 0.395 and 0.629 THz. The configuration of the antenna is based on a traditional fork antenna. At the resonant frequencies, this MIMO antenna can achieve bandwidths of 9.53 GHz and 24.19 GHz, with reflection coefficients of -16.19 dB and -24.27 dB, respectively. Moreover, a gain of 5.17 dB and 3.19 dB are obtained at the second and first resonant frequencies, respectively. In the effort to maintain the operational band and enhance gain, a significant challenge arises from the insufficient isolation between the four antenna elements within the limited space. A Defected Ground Structure (DGS) is constructed and the inter-element distance is carefully investigated in order to effectively address this issue. Mutual coupling effects are effectively reduced with this antenna, and an amazing MIMO diversity response is shown. Additionally, it achieves a mean effective gain of less than -3, envelope correlation coefficients below 0.0125, diversity gain of around 10 dB, and total active reflection coefficients below -4 dB. The suggested design was simulated using the ansys High-Frequency Structure Simulator program. These enhancements show that the recommended MIMO antenna is a suitable choice for terahertz applications like 5 G networks of the future and terahertz imaging systems used in medical settings for tissue imaging and cancer diagnosis.